2014
DOI: 10.1007/s00417-014-2684-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ganglion cell layer and photoreceptor layer using optical coherence tomography after idiopathic epiretinal membrane surgery

Abstract: The postoperative ganglion cell layer was found to be correlated to postoperative VA more consistently than the photoreceptor layer after ERM surgery. The outer retinal damage was a determining factor in the poor VA group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
2
10
1
5
Order By: Relevance
“…The analyses of CMT were inconclusive, to the same extent as previous studies have reported conflicting results related to the association between CMT and visual loss [27,28,29,30,31,32]. All 4 eyes with a decreased EZ signal showed vision loss and ERM progression in our study, and their impaired photoreceptor integrity was related to vision loss [28,29,30].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The analyses of CMT were inconclusive, to the same extent as previous studies have reported conflicting results related to the association between CMT and visual loss [27,28,29,30,31,32]. All 4 eyes with a decreased EZ signal showed vision loss and ERM progression in our study, and their impaired photoreceptor integrity was related to vision loss [28,29,30].…”
Section: Discussioncontrasting
confidence: 58%
“…All 4 eyes with a decreased EZ signal showed vision loss and ERM progression in our study, and their impaired photoreceptor integrity was related to vision loss [28,29,30]. However, vision loss in 2 eyes with an intact EZ signal would be associated with damage to the inner retinal layers [31,32]. Screening of the EZ signal seems to be insufficient to detect early vision loss.…”
Section: Discussionmentioning
confidence: 70%
“…Previous studies reported good surgical outcomes and many prognostic factors, such as preoperative visual acuity, retinal thickness, photoreceptor layer status, and the status of other specific layers of the retina, for the outcome following ERM surgery [13,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32]. Among these, preoperative vision is a well-known prognostic factor that influences postoperative vision.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, surgical outcomes, including ERM patients with a vision better than 20/30, were reported [16,33]. They showed that better initial vision resulted in higher postoperative vision, while poorer initial vision resulted in greater vision improvement, and more patients with poor baseline vision experienced vision improvement after surgery [16,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation